Extending Musical Form Outwards in Space and Time: Compositional strategies in sound art and audiovisual installations - Basanta, Adam (Organised sound : an international journal of music technology, 2015)
Sound and media installations are rarely considered from a time-based, formal perspective. In order to enable a greater understanding of temporal form in sound installations, I suggest a cross-disciplinary adaptation of musical form to the installation context. Due to the differences between concert and installation presentation practices – including, but not limited to, the increased agency of the mobile visitor – I re-examine form in installation contexts as the particular temporal experience co-produced by the first-person subject as they navigate in, through and out of the work’s frame. By applying this musical perspective to macro-scale formal structures, a set of tools and concepts become available for the analysis of temporal form in existing sound or audiovisual installations. Using practice-based observation and analysis, I describe several compositional strategies through which musical concepts of material and form can be extended in space and time: each of these strategies provides means with which to shape or constrain the visitor’s co-production of experiential form. Finally, I discuss several strategies that can be used for the creation of large-scale form, with particular reference to algorithmic design principles used in my recent audiovisual installation, Room Dynamics.